Efficient, scalable, closed-loop synthesis of highly crystalline pure phase MgAl-layered double hydroxides intercalated with hydroxyl anions. Issue 5 (17th January 2022) - Min, Luofu; Duan, Jingying; Liu, Lu; Ge, Sheng; Zhang, Wen; Wang, Yuxin
Abstract : Highly crystalline MgAl-LDH intercalated with hydroxyl anions was attained by a sustainable and scalable method using magnesium oxide and aluminate. The rapid formation of MgAl-LDH followed an interfacial dissolution–reprecipitation mechanism. Abstract : Layered double hydroxides (LDHs) can play an important role in various areas, but conventional LDHs synthesis often causes product agglomeration and generates plenty of high-salt wastewater, and requires a time-consuming aging process to reach the desired purity and crystalline state. Herein, we report the synthesis of MgAl-LDH, a representative of these kinds of ionic lamellar inorganic solids, with a novel method involving the reaction of magnesium oxide (MgO) with aluminate ions (Al(OH)4 − ) in a strongly alkaline environment. The formation of MgAl-LDH follows a mechanism of interfacial dissolution–reprecipitation (IDR), i.e., Mg 2+ ions released at the interface of dissolved MgO react immediately with Al(OH)4 − ions to reprecipitate as MgAl-LDH. The obtained MgAl-LDH has no impurity phases and shows high crystallinity, high specific surface area, and a narrow particle size distribution. Moreover, MgAl-LDH is intercalated with OH − anions, so it can be directly used as a Brønsted base catalyst and ion exchanger. The novel method requires no time-consuming aging process and is highly scalable. It is also shown that a closed-loop synthesis of MgAl-LDH without waste discharge can be achieved with an appropriate Al source, e.g., Al(OH)3, and a recycled NaOH solution.